A phantom for visualization of three‐dimensional drug release by ultrasound‐induced mild hyperthermia. Issue 8 (26th July 2013) - Lai, Chun‐Yen; Kruse, Dustin; Seo, Jai Woong; Kheirolomoom, Azadeh; Ferrara, Katherine W.
Abstract : Purpose: : Ultrasound‐induced mild hyperthermia has advantages for noninvasive, localized and controlled drug delivery. In this study, a tissue‐mimicking agarose‐based phantom with a thermally sensitive indicator was developed for studying the spatial drug delivery profile using ultrasound‐induced mild hyperthermia. Methods: : Agarose powder, regular evaporated milk, Dulbecco's phosphate‐buffered saline (DPBS), n‐propanol, and silicon carbide powder were homogeneously mixed with low temperature sensitive liposomes (LTSLs) loaded with a self‐quenched near‐infrared (NIR) fluorescent dye. A dual‐mode linear array ultrasound transducer was used for insonation at 1.54 MHz with a total acoustic power and acoustic pressure of 2.0 W and 1.5 MPa, respectively. After insonation, the dye release pattern in the phantom was quantified based on optical images, and the three‐dimensional release profile was reconstructed and analyzed. A finite‐difference time‐domain‐based algorithm was developed to simulate both the temperature distribution and spatial dye diffusion as a function of time. Finally, the simulated dye diffusion patterns were compared to experimental measurements. Results: : Self‐quenching of the fluorescent dye in DPBS was substantial at a concentration of 6.25 × 10 −2 mM or greater. The transition temperature of LTSLs in the phantom was 35 °C, and the release reached 90% at 37 °C. The simulated temperature for hyperthermia correlated with the thermocouple measurements with a mean error between 0.03 ± 0.01 and 0.06 ± 0.02 °C. The R 2 value between the experimental and simulated spatial extent of the dye diffusion, defined by the half‐peak level in the elevation, lateral and depth directions, was 0.99 (slope = 1.08), 0.95 (slope = 0.99), and 0.80 (slope = 1.04), respectively, indicating the experimental and simulated dye release profiles were similar. Conclusions: : The combination of LTSLs encapsulating a fluorescent dye and an optically transparent phantom is useful for visualizing and modeling drug release in vitro following ultrasound‐induced mild hyperthermia. The coupled temperature simulation and dye‐diffusion simulation tools were validated with the experimental system and can be used to optimize the thermal dose and spatial and temporal dye release pattern.